Influence of higher time harmonics on the electrical and mechanical performance of an inverter-fed squirrel cage induction motor - Roeber, Jochen Erich (Department of Electrical Engineering, 2016)
Due to the ruggedness, reliability and low maintenance required, small inverter-fed induction motors (1.5 kW to 25 kW) have earned a reputation and are utilized more and more frequently in industry for variable speed applications. The applied voltage and current waveforms are generally quite non-sinusoidal and polluted with higher time harmonic components. The higher time harmonics affect the electrical and mechanical performance significantly, and adverse effects are investigated. Literature on the effect of higher time harmonics is reviewed. Recommendations referring to various aspects under non-sinusoidal excitation are made when installing inverter-fed induction motors. Different inverter supplies (6-Pulse Square Wave voltage source inverter (VSI), PWM VSI and sinusoidal excitation) are used with a small 3-Phase, 3-kW squirrel cage induction motor, configured under synchronous characteristic Vᵣ/50 and subsynchronous characteristic Vᵣ/87. The respective voltage and current frequency spectrums of the excitation source are analyzed and the harmonic content determined. Performance executed under identical operating respectively and results are compared with pure sinusoidal (fundamental) excitation. tests are conditions respect to To determine the electrical performance the efficiency, power factor, temperature rise of the stator and induced shaft voltages were analyzed. The mechanical performance under inverter operation was analyzed by measuring the torque, torque pulsations, critical speeds and resonance frequencies of frame vibrations and torque oscillations as well as vibrations in x-, y-, and z-direction of the inverter-fed induction machine. Consequences of time harmonics on the induction motor and system are discussed. Conclusions on the effect of time harmonics and performance of different inverter types compared to sinusoidal excitation are drawn and are theoretically summarized and justified. Summary in English and German. Bibliography: pages 148-154.